PENGGUNAAN TERAPI KOMPLEMENTER BIRTH BALL TERHADAP PEMBUKAAN SERVIKS PADA IBU BERSALIN PRIMIGRAVIDA - Ervin Rufaindah (Media Husada Journal of Midwifery Science, 2024)
Introduction. One of the complications of childbirth that contributes to maternal mortality is prolonged labor. Various physiological efforts made to prevent prolonged labour, such as pregnancy exercises, deep breathing techniques and the use of birthballs. Birthball means a birth ball that can be used by first-time mothers to their usual position help progress in labour. Birthball can stimulate the opening of the cervix and widen the pelvic outlet. Sit straight on the ball then the force of gravity will help the fetus or the lowest part of the fetus to get down to the pelvis. Objectives. This study aims to determine Effect of complementary therapy with Birth Ball on opening cervix at PMB Yunita Cecilia Malang. Methods. This research uses the method quasi experiment with post test only design with control group design. Subjects in this study were normal primigravida mothers who fulfilled inclusion and exclusion criteria. The size of the research sample is 60 people divided into two intervention and control groups. This research instrument using a questionnaire and partograph. Data analysis using an unpaired difference test. Results. The research results found that After the study, it was found that there was a significant difference in the progress of labor in the two groups (p value = 0.000). Conclusions. So that it can It can be concluded that there is an effect of complementary therapy with a birth ball on the opening of the cervix in women giving birth. It is recommended for mothers who are giving birth practicing complementary therapy exercises while sitting on a maternity ball can recommended as one significant way to improve labor progress. Keywords: birth ball; opening of the cervix; giving birth